Shaoyao decoction alleviates TNBS-induced ulcerative colitis by decreasing inflammation and balancing the homeostasis of Th17/Treg cells - Dongsheng Wu; Yu Zhang; Bo Zou; Yi Lu; Hui Cao (BMC, 2023)
Abstract Background Ulcerative colitis (UC) is a persistent and non-specific inflammatory condition that mainly affects the bowels and has challenging treatment. UC has a growing incidence and significantly affects the well-being of patients. Many medications used to treat UC can disrupt the metabolism and immune system homeostasis, frequently leading to significant adverse effects. Hence, exploring alternative therapies, such as traditional Chinese medicine and probiotics, has recently emerged as a primary research hotspot owing to their safety. Although the therapeutic mechanism of Shaoyao decoction has not been clarified, it has demonstrated a beneficial clinical effect on UC. Aim This study aimed to assess the effect of Shaoyao decoction on a rat model of UC and investigate its underlying mechanisms. Methods The rat model of UC was induced by 2,4,6-trinitrobenzenesulfonic acid (TNBS). The extent of damage to the intestines was assessed using the disease activity index (DAI), colonic mucosa damage index (CMDI), and histological scores. Immunohistochemistry was employed to detect the tissue levels of interleukin (IL)-17, transforming growth factor (TGF)-β1, and IL-10. Additionally, the proportion of Th17 and Treg cells was detected using flow cytometry. In colon tissue, the levels of forkhead box (Fox)p3, RAR-related orphan receptor (ROR)γt, IL-6, p-STAT3, and STAT3 proteins were quantified by Western blotting. Results Treatment with Shaoyao decoction enhanced the overall health of rats and reduced colonic damage. Additionally, Shaoyao decoction significantly alleviated the severity of DAI, CMDI, and HS. The proportion of Th17 cells was reduced, and the proportion of Treg cells was increased by Shaoyao decoction. The expression of IL-17 and RORγt was suppressed by Shaoyao decoction, while the expression of IL-10, TGF-β1, and Foxp3 was increased. The expression of IL-6, p-STAT3, and STAT3 was decreased by Shaoyao decoction. Conclusion The Shaoyao decoction alleviates the symptoms of TNBS-induced UC by decreasing inflammation and mitigating intestinal damage while preserving the balance between Th17 and Treg. Shaoyao decoction modulates the IL-6/STAT3 axis, thereby regulating the balance between Th17 and Treg cells.